Read family papers - Read, George, 1733-1798.; Read, George, 1765-1836.; Read, James, 1743-1822.; Read, John, 1769-1854.; Read, John M. (John Meredith), 1797-1874.; Read, John Meredith, 1837-1896.
Correspondence, deeds and indentures, a journal, notebooks, legal documents, genealogical records, commissions, printed material, and other papers. Papers of George Read relate chiefly to his activities during the American Revolution and his law practice in New Castle, Del. Includes a journal containing memoranda (1782-1784) kept by James Read as secretary of the Continental Congress Marine Committee and a record of his personal accounts (1794-1812). Papers of John Read include a notebook (1809-1818) of correspondence and memoranda which he kept as secretary of the Asylum Company, a land company of Philadelphia, Pa. Those of John Meredith Read pertain primarily to his involvement in Pennsylvania state politics, and papers of John Meredith Read, Jr., include correspondence and genealogical material pertaining to his book about Henry Hudson, correspondence regarding the sale of Read's collection of Robert Morris papers, and English legal documents (1568-1696, undated) from his manuscript collection.
Correspondents include John Bubenheim Bayard, James Buchanan, Thomas Cadwalader, Simon Cameron, George Clymer, John Dickinson, Philemon Dickinson, Joseph Galloway, Ulysses S. Grant, Gouverneur Kemble, Abraham Lincoln, Mary Todd Lincoln, Samuel Meredith, John G. Nicolay, Caesar Rodney, Tench Tilghman, Samuel Wharton, James Wilson, and John Witherspoon.
Library of Congress Rare Book and Special Collections Division.
Read (Reed) family of New Castle, Del., later of Pennsylvania. Family members represented include George Read (1733-1798), lawyer, delegate to the U.S. Continental Congress, signer of the Declaration of Independence, and U.S. senator from Delaware; his brother, James Read (1743-1822), army officer, banker, and merchant, of Philadelphia, Pa.; George Read's sons, John Read (1769-1854), banker, lawyer, and Pennsylvania public official, and George Read (1765-1836), lawyer and Delaware public official; John Read's son, John M. Read (1797-1874), jurist and Pennsylvania public official; and John Meredith Read, Jr. (1837-1896), army officer, diplomat, and lawyer.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Bayard, John Bubenheim, -- 1738-1807 -- Correspondence; Buchanan, James, -- 1791-1868 -- Correspondence; Cadwalader, Thomas, -- 1707 or 1708-1779 -- Correspondence; Cameron, Simon, -- 1799-1889 -- Correspondence; Clymer, George, -- 1739-1813 -- Correspondence; Dickinson, John, -- 1732-1808 -- Correspondence; Dickinson, Philemon, -- 1739-1809 -- Correspondence; Galloway, Joseph, -- 1731-1803 -- Correspondence; Grant, Ulysses S. -- 1822-1885 -- Correspondence; Hudson, Henry, -- -1611.; Hudson, Henry, -- -1611 -- Correspondence; Kemble, Gouverneur, -- 1786-1875 -- Correspondence; Lincoln, Abraham, -- 1809-1865 -- Correspondence; Lincoln, Mary Todd, -- 1818-1882 -- Correspondence; Meredith, Samuel, -- 1741-1817 -- Correspondence; Morris, Robert, -- 1734-1806.; Morris, Robert, -- 1734-1806 -- Correspondence; Nicolay, John G. -- 1832-1901 -- Correspondence; Rodney, Caesar, -- 1728-1784 -- Correspondence; Tilghman, Tench, -- 1744-1786 -- Correspondence; Wharton, Samuel, -- 1732-1800 -- Correspondence; Wilson, James, -- 1742-1798 -- Correspondence; Witherspoon, John, -- 1723-1794 -- Correspondence; Hudson family; Reed family; United States. -- Continental Congress; United States. -- Continental Congress. -- Marine Committee; Asylum Company; Land companies -- Pennsylvania -- Philadelphia; Legal instruments -- England; Practice of law -- Delaware; Delaware -- Social life and customs; New Castle (Del.) -- Social life and customs; Pennsylvania -- Politics and government; United States -- History -- Revolution, 1775-1783.